1998
DOI: 10.1207/s15327655jchn1504_6
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Migrant Voices: Focus Groups on Health issues in South Georgia

Abstract: This qualitative study utilized focus groups to invite Latino migrant farm workers to express ideas about their health and service needs. Four focus groups composed of Latino men and women were conducted on four different evenings in the same county. Three themes emerged: health care issues, living and working conditions, and social and community issues. Specific needs of the community were also identified by the participants. For the first time, migrant farm workers in Georgia had the opportunity to lend thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 5 publications
(5 reference statements)
1
46
0
Order By: Relevance
“…Many of the findings from this study are consistent with the findings reported in the other two studies that used focus group methods to understand health care needs of Latinos living in rural areas of the United States, although there were several unique themes identified by the parents in this study. Themes that were consistent with those identified by Blewett et al (2003) and by Perilla et al (1998) included the cost of health care, lack of insurance, language barriers, use of home remedies, inadequate health and dental services, deterioration of family values, racism or prejudice, and attitudes of health care providers that preclude development of positive and trusting relationships. Because many Latino patients place a high value on the quality of the relationship with their health care providers (respeto), this finding suggests that care may be adversely affected by the perception of negative or patronizing attitudes.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Many of the findings from this study are consistent with the findings reported in the other two studies that used focus group methods to understand health care needs of Latinos living in rural areas of the United States, although there were several unique themes identified by the parents in this study. Themes that were consistent with those identified by Blewett et al (2003) and by Perilla et al (1998) included the cost of health care, lack of insurance, language barriers, use of home remedies, inadequate health and dental services, deterioration of family values, racism or prejudice, and attitudes of health care providers that preclude development of positive and trusting relationships. Because many Latino patients place a high value on the quality of the relationship with their health care providers (respeto), this finding suggests that care may be adversely affected by the perception of negative or patronizing attitudes.…”
Section: Discussionmentioning
confidence: 69%
“…Some of the study participants reported returning to Mexico to get care that they could not get in the United States. Perilla, Wilson, Wold, and Spencer (1998) conducted four focus groups with Latino migrant farm workers in South Georgia and identified similar barriers to health care access. Other health care issues identified by Perilla et al included lack of dental and eye care services, transportation problems, tobacco illnesses, and lack of information about sexually transmitted diseases and AIDS.…”
mentioning
confidence: 99%
“…Only a single study (104) reports using the classic conceptual framework of health services research, the health behavior model (1, 4), to investigate the health services needs or utilization of farmworkers. A handful of analyses document general health services for farmworker communities (24,57,78,89,96,107). Several studies document farmworkers' dental health services needs (31,58,79,101).…”
Section: Research On Farmworker Health Servicesmentioning
confidence: 99%
“…For example, one study (57) emphasizes the need for family planning and food programs, whereas another (107) delineates the importance of personal (e.g., language and education) and financial (e.g., health insurance) resources in the utilization of subsidized migrant clinics. A third study (78) discusses the importance of obtaining information about health care needs directly from farmworkers. The need for eye care is highlighted by a CAWHS finding that more than two thirds of farmworkers surveyed had never had an eye examination (101).…”
Section: Research On Farmworker Health Servicesmentioning
confidence: 99%
“…As a formative research activity, researchers conducted five focus groups with female nursery and fernery workers in order to enhance knowledge of attitudes and practices related to occupational risks and pregnancy health and to gather qualitative data that could help form a survey instrument. Focus groups have been used effectively with socially marginalized groups such as farmworkers as a means to elicit open-ended responses related to experiences, perceptions, behaviors, and knowledge which provide greater depth and richness than quantitative data [36][37][38][39].…”
Section: Data Collectionmentioning
confidence: 99%